Biomarkers in osteoarthritis - Mobasheri, Ali (Henry Stewart Talks, 2013)
Diagnosis of osteoarthritis, Issues with radiographic diagnosis, Lack of analytical tools and reagents for diagnosis, Limitations of current biomarkers, Future opportunities for the pharmaceutical industry